On Some Controversial Problems of the Syntax of the Armenian Language - Zakaryan, Hovhannes (Bulletin of Yerevan University B: Philology, 2022)
This article is about the following three issues.1. Linguistic linear units, according to their position, do not have three characteristics: prepositive, interpositive, and postpositive, but four. The fourth is the peripositive position when the characterized unit surrounds another unit.Considered parenthetical (inserted) units those interpositive constructions, that are main clauses in the prepositive position, actually have the same meaning and perform the same function in any position.In Armenian, there are such complex sentences, in which the subordinate clause occupies not only prepositive, interpositive and postpositive positions in relation to the main clause, but it can also happen in the peripositive position: Ընկերներս, կարծում եմ, (որ) ինձ մենակ չեն թողնի: Իմ ծննդավայրում, արդեն հինգ տարի է, (ինչ) չեմ եղել. The latter, however, either haven't been discussed till nowadays in linguistic literature or have been considered simple sentences with parenthetical clauses. It means that the principal clause, being in an interpositive position compared to the subordinate clause, has been considered to be such a syntactic unit that remains outside the limits of the sentence's grammatical structure.In Armenian there are also peripositive participial phrases: Միայնակ ես սիրում եմ նստել երերուն լույսերում:The conjunctions սակայն, ուրեմն, acquiring a modal connotation in an interpositive or postpositive position, do not lose their role as conjunction and do not acquire part-of-speech homonymy.
Keywords: relative position; prepositive; interpositive; postpositive; peripositive (position); principal clause; parenthetical unit; modal word; conjunction; part-of-speech homonymy